Addressing Cybersecurity Challenges in Education - Triplett, William J (International Journal of STEM Education for Sustainability, 2023)
This study aimed to address the challenges of cybersecurity in education. As kindergarten through twelfth-grade education shifts to online and remote learning, educators and governments are increasingly vulnerable to the risks of cyberattacks and cybercrimes. This study focused on the strategies that institutions can employ to increase their students’ cybersecurity awareness and simultaneously motivate them to pursue cybersecurity as a career. To achieve the research objectives, a systematic review of ten studies was performed, and the results showed that game-based strategies were effective in increasing students’ awareness about cybersecurity and their interest in pursuing cybersecurity as a career. The study’s implications suggest that game designers and developers may want to develop advanced games that gauge students’ cybersecurity skills and ability to respond to aggressive forms of cyberattacks in addition to enhancing their knowledge of cybersecurity.